Saprophytic and Potentially Pathogenic Fusarium Species from Peat Soil in Perak and Pahang - Nurul Farah Abdul Karim; Masratulhawa Mohd; Nik Mohd Izham Mohd Nor; Latiffah Zakaria (Tropical Life Sciences Research, 2016)
Isolates of Fusarium were discovered in peat soil samples collected from peat swamp forest, waterlogged peat soil, and peat soil from oil palm plantations. Morphological characteristics were used to tentatively identify the isolates, and species confirmation was based on the sequence of translation elongation factor-1? (TEF-1?) and phylogenetic analysis. Based on the closest match of Basic Local Alignment Search Tool (BLAST) searches against the GenBank and Fusarium-ID databases, five Fusarium species were identified, namely F. oxysporum (60%), F. solani (23%), F. proliferatum (14%), F. semitectum (1%), and F. verticillioides (1%). From a neighbour-joining tree of combined TEF-1? and ?-tubulin sequences, isolates from the same species were clustered in the same clade, though intraspecies variations were observed from the phylogenetic analysis. The Fusarium species isolated in the present study are soil inhabitants and are widely distributed worldwide. These species can act as saprophytes and decomposers as well as plant pathogens. The presence of Fusarium species in peat soils suggested that peat soils could be a reservoir of plant pathogens, as well-known plant pathogenic species such F. oxysporum, F. solani, F. proliferatum, and F. verticillioides were identified. The results of the present study provide knowledge on the survival and distribution of Fusarium species. Pencilan Fusarium telah dipencilkan daripada sampel tanah gambut yang diperolehi dari hutan paya gambut, tanah gambut takung air, dan tanah gambut ladang kelapa sawit. Pencirian secara morfologi digunakan untuk mengenal pasti pencilan tersebut secara tentatif dan penentuan spesies berdasarkan jujukan gen faktor pemanjangan translasi-1? (TEF-1?) dan analisis filogenetik. Berdasarkan padanan yang terdekat carian Basic Local Alignment Search Tool (BLAST) pangkalan data Genbank dan Fusarium-ID, lima spesies Fusarium telah dikenal pasti iaitu F. oxysporum (60%), F. solani (23%), F. proliferatum (14%), F. semitectum (1%), dan F. verticillioides (1%). Daripada analisis filogenetik penyambung jiran menggunakan gabungan jujukan gen TEF-1? dan ?-tubulin, menunjukkan pencilan dari spesies yang sama dikelompokkan dalam klad yang sama walaupun variasi intraspesies diperhatikan melalui analisis filogenetik. Spesies Fusarium yang dipencilkan dalam kajian ini adalah penghuni tanah dan tersebar meluas di seluruh dunia, dan boleh menjadi saprofit dan pengurai. Kehadiran spesies Fusarium dalam tanah gambut mencadangkan tanah gambut boleh menjadi takungan patogen tumbuhan di mana beberapa spesies patogen tumbuhan terkenal seperti F. oxysporum, F. solani, F. proliferatum, dan F. verticillioides telah dikenal pasti. Keputusan kajian ini juga memberikan pengetahuan tentang kemandirian dan penyebaran spesies Fusarium.